A bijective soft set theoretic approach for concept selection in design process. (1st February 2017) - Tiwari, Varun; Jain, Prashant Kumar; Tandon, Puneet
ABSTRACT: The problem of decision-making in an uncertain environment during early design stages has found paramount importance in recent years. A novel method based on soft set theory is developed and proposed here, for concept selection during the early phase of product design. The advantage of soft set theory to describe the features of an object through any approximations is used in the proposed method to incorporate qualitative judgements of decision-makers. Bijective soft sets are used in the proposed work to depict mapping between customer requirements and generated design concepts. The method proposes the construction of a correlation table from a bijective soft set in a parametric sense. Correlation table helps the designers to identify the effect of conflicting requirements of different customers. The union and intersection operations are then performed on the correlation table which are called here as Row Union (RUnion), Row Intersection (RIntersection), Column Union (CUnion), and Column Intersection (CIntersection). A RUnion and CUnion operation on correlation table helps the designer to identify all the potential concepts which are suboptimal choices based on customer requirements. After performing RUnion and CUnion operations, RIntersection and CIntersection are performed to identify optimal choice(s) which could meet maximum conflicting requirements of customers.